MUC1 mediates Pneumocystis murina binding to airway epithelial cells. (19th February 2020) - Liu, Yueqin; Davis, A. Sally; Ma, Liang; Bishop, Lisa; Cissé, Ousmane H.; Kutty, Geetha; Kovacs, Joseph A.
Abstract: Previous studies have shown that Pneumocystis binds to pneumocytes, but the proteins responsible for binding have not been well defined. Mucins are the major glycoproteins present in mucus, which serves as the first line of defence during airway infection. MUC1 is the best characterised membrane‐tethered mucin and is expressed on the surface of most airway epithelial cells. Although by electron microscopy Pneumocystis primarily binds to type I pneumocytes, it can also bind to type II pneumocytes. We hypothesized that Pneumocystis organisms can bind to MUC1 expressed by type II pneumocytes. Overexpression of MUC1 in human embryonic kidney HEK293 cells increased Pneumocystis binding, while knockdown of MUC1 expression by siRNA in A549 cells, a human adenocarcinoma‐derived alveolar type II epithelial cell line, decreased Pneumocystis binding. Immunofluorescence labelling indicated that MUC1 and Pneumocystis were co‐localised in infected mouse lung tissue. Incubation of A549 cells with Pneumocystis led to phosphorylation of ERK1/2 that increased with knockdown of MUC1 expression by siRNA. Pneumocystis caused increased IL‐6 and IL‐8 secretion by A549 cells, and knockdown of MUC1 further increased their secretion in A549 cells. Taken together, these results suggest that binding of Pneumocystis to MUC1 expressed by airway epithelial cells may facilitate establishment of productive infection.